Dynamics of zebrafish fin regeneration using a pulsed SILAC approach. Issue 4 (February 2015) - Nolte, Hendrik; Hölper, Soraya; Housley, Michael P.; Islam, Shariful; Piller, Tanja; Konzer, Anne; Stainier, Didier Y. R.; Braun, Thomas; Krüger, Marcus; Krijgsveld, Jeroen
<x xml:space="preserve">Abstract</x> The zebrafish owns remarkable regenerative capacities allowing regeneration of several tissues, including the heart, liver, and brain. To identify protein dynamics during fin regeneration we used a pulsed SILAC approach that enabled us to detect the incorporation of 13C6‐lysine (Lys6) into newly synthesized proteins. Samples were taken at four different time points from noninjured and regrowing fins and incorporation rates were monitored using a combination of single‐shot 4‐h gradients and high‐resolution tandem MS. We identified more than 5000 labeled proteins during the first 3 weeks of fin regeneration and were able to monitor proteins that are responsible for initializing and restoring the shape of these appendages. The comparison of Lys6 incorporation rates between noninjured and regrowing fins enabled us to identify proteins that are directly involved in regeneration. For example, we observed increased incorporation rates of two actinodin family members at the actinotrichia, which is a hairlike fiber structure at the tip of regrowing fins. Moreover, we used quantitative real‐time RNA measurements of several candidate genes, including osteoglycin, si:ch211–288h17.3, and prostaglandin reductase 1 to correlate the mRNA expression to Lys6 incorporation data. This novel pulsed SILAC methodology in fish can be used as a versatile tool to monitor newly synthesized proteins and will help to characterize protein dynamics during regenerative processes in zebrafish beyond fin regeneration.